2022
DOI: 10.1016/j.cell.2022.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple early factors anticipate post-acute COVID-19 sequelae

Abstract: Post-acute sequelae of COVID-19 (PASC) represent an emerging global crisis. However, quantifiable risk-factors for PASC and their biological associations are poorly resolved. We executed a deep multi-omic, longitudinal investigation of 309 COVID-19 patients from initial diagnosis to convalescence (2-3 months later), integrated with clinical data, and patient-reported symptoms. We resolved four PASC-anticipating risk factors at the time of initial COVID-19 diagnosis: type 2 diabetes, SARS-CoV-2 RNAemia, Epstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
795
3
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 816 publications
(951 citation statements)
references
References 82 publications
28
795
3
18
Order By: Relevance
“…The exertion intolerance and other ME/CFS symptoms might also be caused by virally induced autoimmunity [ 62 , 63 ]. Interestingly enough, similar mechanisms are also thought to play a part in the development of long COVID [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exertion intolerance and other ME/CFS symptoms might also be caused by virally induced autoimmunity [ 62 , 63 ]. Interestingly enough, similar mechanisms are also thought to play a part in the development of long COVID [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“… Studies to date have identified certain factors that predict whether an individual with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection will fully recover or develop post-acute sequelae, including the persistent symptoms that characterize long COVID. Shown here are several mechanisms with evidence supported by recent studies of individuals with post-acute sequelae of SARS-CoV-2 infection (PASC) [ 1 , 4. , 5.…”
mentioning
confidence: 70%
“…The authors have no interests to declare. 1 Division of HIV, Infectious Diseases, and Global Medicine,…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ). Also, having Long COVID is in itself associated with a weaker antibody response to infection and immune dysregulation [7][8][9] . Thus, it is not scientifically sound to use antibody testing to classify the exposure (past SARS-CoV-2 infection) in relation to the occurrence of the outcome (persistent symptoms), because the method used for classification itself may be causing the outcome if the aetiology of Long COVID is related to the nature of the immune response to the infection.…”
mentioning
confidence: 99%